(untitled) (Eurasian Journal of Philology Science and Education, 2020)
This paper is devoted to complex constructions with the conjunctions as if and as though, which are viewed differently by different scholars. The semantic ambiguity of the conjunctions as if and as though enables the linguists to define the subordinate sentences introduced by these conjunctions as the subordinate clauses of unreal condition, of manner or of manner and unreal condition. Syntactically the constructions under analysis embrace sentences with the predicative, adverbial and appositive subordinate clauses, which, as a rule, are analyzed as separate syntactic types. The author of the article considers it expedient to qualify constructions under analysis as complex sentences with unreal comparison on the ground that the semantic structure of the conjunctions contains the semes of comparison, supposition and сondition. The transformation method, as well as the analysis of lexical factors, grammatical and punctuation peculiarities, has made it possible to state that these subordinate clauses are characterized by a semantic syncretism: alongside with the meaning of unreal comparison they can express manner, cause, purpose, concession and qualitative characteristics. The author claims that semantic syncretism of the subordinate clauses introduced by the conjunctions as if and as though can be considered a distinctive feature of the constructions with unreal comparison, which allows to combine them into a separate group.